Selection of Sub1 locus for submergence-tolerant introgression in a backcrossing of South Sumatra rice based on SSR markers - Adriansyah, Fikri; Hasmeda, Mery; Suwignyo, Rujito Agus; Halimi, Entis Sutisna; Fatimah,; Wibisono, Imam; Sarimana, Upit (Penerbit Universiti Kebangsaan Malaysia, 2022)
The development of a new submergence-tolerant variety is one ideal solution to reduce submergence stress impact caused by the unpredictable occurrence of flooding in the South Sumatra riparian wetland rice cultivation area. The Sub1 gene for submergence tolerance was introgressed into South Sumatra riparian wetland rice from the donor parent FR13A using marker-assisted backcrossing. This study involves a backcrossing between Pelita Rampak and BC1F1 Pelita Rampak, FR13A-derived Sub1 breeding lines. The main objective of this study was to introgress the Sub1 gene in BC2F1 using marker-assisted selection (MAS). The introgression of the Sub1 gene in the backcrossed lines was confirmed by the tightly linked markers RM219 and RM23915. The segregation ratio of RM219 was a good fit to the expected 1:1 Mendelian single-gene model (DF = 1.0, p ≤ 0.05). In the background study, out of 237 SSR markers unlinked to the target loci, 84 were found to be polymorphic between the two parents and were used for background selection among the selected progeny. Recurrent parent genome recovery in the backcrossed lines ranged from 57.1% to 72.6%. Improvements in the tiller number, percentage of filled grain, productive tiller number and percentage of tiller number were found on these backcrossed lines. The five best backcrossed lines were selected based on SSR markers, submergence tolerance, phenotypic study and agronomic performance.